A comprehensive index to assess the sustainability of water and sanitation management systems - Iribarnegaray, Martín Alejandro (2012)
A comprehensive sustainability index for the assessment of water and sanitation management systems (WSMS) is presented. The index was based on a conceptual framework that perceives sustainability as a combination of territorial, temporal, and personal aspects. A set of sustainability indicators was selected in agreement within this framework, and the 'Water and Sanitation Sustainability Index' (WASSI) was built. The WASSI was used to assess the sustainability of the WSMS of the city of Salta, Argentina. Indicators were calculated from information gathered by several means including literature reviews, questionnaires, visits, and participatory workshops. The index was sensitive to detect variations between different aspects of the local WSMS. It was also relatively independent to the quantity and quality of the information available. The WASSI could be a useful tool to assess and improve sustainability of water and sanitation throughout the management systems. © IWA Publishing 2012.